Examples Of Benchmarking From Strategic Management Tools In Akhism - Ali Erbaşı; Süleyman Ersöz (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Strategic management has been in the limelight for businesses in recent years. Majority of businesses set sight on strategic management, gaining competitive capacity, searching to increase their successes. In parallel with these advances, numerous tools to be used in strategic management have emerged. In this context, using the strategic management tools in business are continues to increase with each passing day. One of these tools is benchmarking. Within having no direct translation for the term ‘benchmarking’ in Turkish language, benchmarking is to adapt an application in certain area into its own management structure by investigating the processes of the management, which applies them in the best way, instead of discovering that application. According to viewpoint of benchmarking, available and previous applications may bring some most important gains in terms of saving time and resource on condition that they are adapted into the culture of that management. In the last quarter of 20th century, benchmarking that emerged as a strategic management tool, is not a strange technique for Turkish culture. Although debates that benchmarking is originated from Japan or Chinese in literature continue, we think that benchmarking is a technique, many practices of which have been carried out, and that has been handled in Akhism philosophy enhanced by Ahi Evran-i Veli in Anatolia of 13th century. Benchmarking technique corresponds to Akhism in many points, put forward by Akhi Evran-i Veli. The aim of this study is to propound that benchmarking, one of the problem-solving tools in total quality management and a strategic management tool, which is quite popular in 21st century, was functioned in 13th century with Akhism philosophy. Different authors deal with the same type of benchmarking under different terms although the classifications on benchmarking are different according to them. In this view, this study is conducted by basing on intrinsic, competitive, functional and generic benchmarking according to the partner selected without causing any further controversy. Within this scope, this benchmarking classification accepted in literature was based on and usages of all benchmarking types in Akhism philosophy were probed with examples. Therefore, the example applications in Akhism are compared with the benchmarking technique in our modern management literature. Consequently, benchmarking was surmised to have been a technique, originated from Akhism. We also believe that it will contribute a lot to the management literature if Akhi philosophy is investigated thoroughly within the framework of management